Team Development Using Open-System Group Model - Satria Efandi (Psyche 165 Journal, 2021)
Team management is needed to support the achievement of organizational goals. One form of good team management also includes efforts to understand and develop the team. The purpose of team development is to ensure that the team can consistently produce the required performance to help organizational processes. This study uses the Open-System model as an effort to understand and carry out team development. The object of this study is the components in one of the teams, namely the Human Resource Development (PSDM) team with team members and the team's environmental conditions. The data collection methods used were interviews with team members, observations of the team's work environment, and document studies on team performance profiles. Data analysis is carried out by integrating findings that have been categorized based on the Open-System model qualitatively. The findings of this study indicate that the Open-System model is able to provide a structured picture of the condition and performance of the HRD team. The main problem condition is that the team work target is not yet solid. The intervention used in responding to the team's assessment results is the preparation of team performance targets using special key performance indicators for the team, so this research is very helpful in developing excellent performance.